Aktivitas biologi enam jenis ekstrak tumbuhan famili Asteraceae terhadap larva Spodoptera litura Fabricius (Lepidoptera: Noctuidae) - Ratna Sari Dewi; Dadang Dadang (Perhimpunan Entomologi Indonesia, 2005)
Biological Activity of Six Plan Extract from Asteraceae on Spodoptera litura Fabricius (lipedoptera : Noctuidae) Larvae. Asteraceae is one of plant family that is known to have insecticidal activity to several insect pests, such as Parthenium argentatum, Crysanthemum cineariaefolium, and Agerantum houstoneanum. The aim of this study is to explore other asteraceae species in other to search for insecticidal activity to Spodoptera litura Fabricius (Lepidoptera: Noctuidae). Six species, Blumea balsamifera (leaf), Elephantopus scaber (leaf), Gynura procumbens (leaf) Artemisia vulgaris (leaf) Soncbus arvensis (leaf) and Helianthus annus (seed) were use in this study. Plant extract were obtained by meseration method using menthanol. The extract were bioassayed to the second instar larvae of S. litura to evaluate the mortality, antifeedant and growth regulation activity. Extract of B. balsamifera and E. scaber have high antifeedant activity at 5 % by reducing larval feeding 87.7% and 81.8% in no choice test, and 94.1% and 86.1% in choice test method, respectively Extract of H. annus, A. vulgaris, and E. scaber prolonged the development of larvae by 4.9, 4.1, 3.9 days, respectively. While extract of H. annus caused mortality of larvae by 86% at 5%.